\(\sqrt{9765+\sqrt{1296}}+\sqrt{15+\sqrt{95481}}+\sqrt{1271+\sqrt{625}}\)
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Những câu hỏi liên quan
15 tháng 8 2023
a: \(=\sqrt[3]{\dfrac{5}{625}}=\sqrt[3]{\dfrac{1}{125}}=\dfrac{1}{5}\)
b: \(=\sqrt[5]{\left(-\sqrt{5}\right)^5}=-\sqrt{5}\)
7 tháng 7 2021
a, \(=>3-\sqrt{2}+\sqrt{50}=3-\sqrt{2}+5\sqrt{2}=3+4\sqrt{2}\)
b, \(=>\dfrac{\sqrt[3]{125.5}}{\sqrt[3]{5}}-\sqrt[3]{\left(-4\right).2}=\sqrt[3]{125}-\sqrt[3]{\left(-2\right)^3}\)
\(=5-\left(-2\right)=7\)
c, \(=>\sqrt{6}.\sqrt{\dfrac{6}{2}}-\sqrt{2}-3\sqrt{4.2}=\sqrt{6}.\sqrt{3}-\sqrt{2}-6\sqrt{2}\)
\(=\sqrt{18}-7\sqrt{2}=3\sqrt{2}-7\sqrt{2}=-4\sqrt{2}\)
d, \(=>\dfrac{\sqrt{3}\left(\sqrt{2}-1\right)}{\sqrt{2}-1}-\dfrac{2}{\sqrt{3}-1}=\sqrt{3}-\dfrac{2}{\sqrt{3}-1}\)
\(=\dfrac{3-\sqrt{3}-2}{\sqrt{3}-1}=\dfrac{1-\sqrt{3}}{\sqrt{3}-1}=-1\)
NC
4
\(\sqrt{9765+\sqrt{1296}}+\sqrt{15+\sqrt{95481}}+\sqrt{1271+\sqrt{625}}\)
\(=\sqrt{9765+\sqrt{36^2}}+\sqrt{15+\sqrt{309^2}}+\sqrt{1271+\sqrt{25^2}}\)
\(=\sqrt{9765+36}+\sqrt{15+309}+\sqrt{1271+25}\)
\(=\sqrt{9801}+\sqrt{324}+\sqrt{1296}\)
\(=\sqrt{99^2}+\sqrt{18^2}+\sqrt{36^2}\)
\(=99+18+36\)
\(=117+36\)
\(=153\)